Peningkatan Kualitas Penyusunan Laporan Keuangan UMKM Melalui Aplikasi Pencatatan Dan Pelaporan Keuangan SIAPIK (Pada UMKM Anyaman Menday Gallery & Souvenir) - Sri Rahayu; Henny Triastuti Kurnianingsih; Farida Khairani Lubis; Eva Harlia; Suginam (JPM: Jurnal Pengabdian Masyarakat, 2022)
Small & Medium-Sized Enterprises (SMEs) face obstacles in preparing financial reporting according to standards, they do not know how much pure profit they will get, they do not understand basic knowledge of financial records, they do not understand financial application knowledge, and they have difficulty obtaining financing from financial institutions. The purpose of this community service is to increase understanding of basic knowledge of financial recording and improve the ability to operate financial applications through education and training in financial accounting based on the SIAPIK Financial Recording and Reporting application. The community service involved the SMEs of Wicker Menday Gallery & Souvenirs as well as Assistance in Dusun III Pantai Cermin. This community service is to explain and inform SIAPIK to UMKM Woven so that it can produce financial reports that are easier for both internal and banking needs. The method used in the training is a face-to-face & mentoring method, namely by analyzing and problem solving. Financial bookkeeping material is presented with lectures, training, questions and answers, demonstrations, and solving cases. The material is made in a simple and attractive way so that financial accounting material is easy for SMEs to understand. The results in training and mentoring are that, first, using SIAPIK is easy and can be used on several devices; secondly, the SIAPIK application can generate financial reports and financial analysis that can be used for internal or external purposes. However, SIAPIK needs to be assisted on an ongoing basis because the financial literacy and digital literacy of SMEs are not evenly distributed as a whole.